(untitled) (Journal of Scientific Research, 2011)
Dissolved arsenic concentrations in the Ganges, Brahmaputra Rivers and confluence of these two rivers show important seasonal variations and maximum arsenic concentrations are observed during the monsoon season (July–October). These seasonal variations of dissolved arsenic concentrations were closely related to intense river-water discharge during the monsoon season with high arsenic-rich suspended particulate matter (SPM) loads. These arsenic-rich SPM mainly are primarily originated from erosion of agricultural land in upstream region irrigated with arsenic contaminated shallow groundwater and to some extent weathering of bed rocks. Considerable amount of iron and manganese enriched SPM adsorbs arsenic and increased water temperature in the summer accelerates microbially-mediated reduction of arsenic (V) to more soluble arsenic (III). Additionally, dissolution of solid arsenic-bearing mineral phases also attributes to high arsenic concentrations in water and causes seasonal variations. It is realized that the SPM of these two major rivers primarily controls the arsenic inputs into the Ganges-Brahmaputra-Meghna delta system. The cycling of arsenic in this delta is related to the monsoon seasonal dynamics, land use patterns and biogeochemical processes. Keywords: Arsenic; Ganges; Brahmaputra; Seasonal variation; Bangladesh. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i1.7820 J. Sci. Res. 4 (1), 65-75 (2012)